2001
DOI: 10.7863/jum.2001.20.6.577
|View full text |Cite
|
Sign up to set email alerts
|

Importance of evaluating organ parenchyma during screening abdominal ultrasonography after blunt trauma.

Abstract: Objective. To determine the benefit of screening ultrasonography for parenchymal abnormalities as well as free fluid during screening abdominal ultrasonography in patients with blunt trauma. Methods. A total of 2693 patients with blunt trauma who were triaged to a level 1 trauma center underwent screening abdominal ultrasonography in the resuscitation suite. Examinations were performed by experienced sonographers and included a screen for free intraperitoneal fluid and evaluation of the abdominal organ parench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 17 publications
0
24
1
1
Order By: Relevance
“…Isolated solid-organ injuries without hemoperitoneum are much more difficult to detect. Brown et al [50] reported on 2693 blunt trauma patients and found that 26% of the patients with injuries had no hemoperitoneum. They also found that they could detect subtle findings of injury in 46% of those patients, including parenchymal injuries and retroperitoneal fluid.…”
Section: Parenchymal and Bowel Injuriesmentioning
confidence: 99%
“…Isolated solid-organ injuries without hemoperitoneum are much more difficult to detect. Brown et al [50] reported on 2693 blunt trauma patients and found that 26% of the patients with injuries had no hemoperitoneum. They also found that they could detect subtle findings of injury in 46% of those patients, including parenchymal injuries and retroperitoneal fluid.…”
Section: Parenchymal and Bowel Injuriesmentioning
confidence: 99%
“…Emergency US performed to detect haemoperitoneum is termed focused assessment with sonography for trauma (FAST) and has 81%-94% sensitivity, 88%-100% specificity and 86%-98% diagnostic accuracy [11][12][13][14][15][16]. Its major limitation is its poor sensitivity (41%-44%) in the direct depiction of solid abdominal organ lesions [17][18][19]. Whereas it is generally recognised that US has a key role in unstable patients [20], its use in stable patients remains controversial owing to its inability to exclude abdominal organ lesions, even in the presence of negative findings, with the result that patients need to undergo contrast-enhanced computed tomography (CT).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been performed to evaluate the reliability of ultrasound for directly visualizing injuries within the abdomen. One included 2693 patients with blunt abdominal trauma: the sensitivity of ultrasound to abdominal injury was only 43% compared to CT or other standards such as laparotomy and autopsy [5]. This also applies to children [6]; in this study the advantages of ultrasound are mentioned; it is quickly performed and less frightening to an injured child than a CT examination.…”
Section: Focused Assessment Sonography In Traumamentioning
confidence: 96%